Causal and non-causal explanations in code biology - Zámečník, Lukáš (Bio Systems, 2021)
In the philosophy of science, we can consider debates about the nature of non-causal explanations in general (e.g. Reutlinger, Saatsi 2018; Lange 2017) and then especially those in the life sciences (e.g. Huneman, 2018; Kostić 2020). These debates are accompanied by the development of a new mechanism that is becoming the major response to the nature of scientific explanation in the life sciences (e.g. Craver, Darden 2013; Craver 2006); and also by the development of a design explanation (e.g. Eck, Mennes 2016) that represents a modern variant of a functional explanation. In this paper, we will methodically: 1. evaluate the plurality of explanatory strategies in contemporary science (chapter 2). 2. describe the mechanical philosophy and mechanistic explanation (Glennan 2016; Craver, Darden 2013, etc.) (chapter 3). 3. explicate the role of mechanisms in code biology (Barbieri 2015, 2002, etc.) and its relation to the new mechanism (chapter 4). 4. fulfill the main goal of the paper - to apply mechanistic explanations in code biology (Barbieri 2019, etc.) and to apply their suitability for this scientific domain (chapter 5).
Keywords: Animals; biologické modely; biologické vědy; biologická evoluce; Code biology; Philosophy; Biological Science Disciplines; Biology; biologie; filozofie; lidé; Models, Biological; Causality; kauzalita; ‘Why’-questions; Mechanistic and design explanation; Causal and non-causal explanation; Biological sciences; zvířata; Biological Evolution; Humans